2020
DOI: 10.1111/ppl.13109
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced N‐metabolites, ABA and IAA‐conjugate in anthers instigate heat sensitivity in spring wheat

Abstract: Unraveling the metabolic and phytohormonal changes in anthers exposed to heat stress would help identify mechanisms regulating heat stress tolerance during the sensitive reproductive stage. Two spring wheat genotypes contrasting for heat tolerance were exposed to heat stress during heading in controlled environment chambers. Anthers were collected from main and primary spikes for metabolic and phytohormonal profiling. A significant reduction in seed set (38%), grain number (54%) and grain weight (52%) per plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The responses of plants to high temperatures have been described in many cases. These include, among others, various well‐known processes such as the appearance of heat shock proteins (HSPs), activation of the antioxidant system, induction of stress hormones, such as abscisic acid (ABA), at the expense of cytokinins (Yang et al 2019, Bheemanahalli et al 2020, Prerostova et al 2020), etc. Changes in the photosynthetic machinery at high temperatures have also been intensively studied (Allakhverdiev et al 2008, Hu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The responses of plants to high temperatures have been described in many cases. These include, among others, various well‐known processes such as the appearance of heat shock proteins (HSPs), activation of the antioxidant system, induction of stress hormones, such as abscisic acid (ABA), at the expense of cytokinins (Yang et al 2019, Bheemanahalli et al 2020, Prerostova et al 2020), etc. Changes in the photosynthetic machinery at high temperatures have also been intensively studied (Allakhverdiev et al 2008, Hu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of endogenous ABA under drought stress conditions have been reported in many plant species, which include grain crops like sorghum [ 215 ], rice [ 216 ], barley [ 217 ], the soybean [ 218 ], and wheat [ 219 ]. The level of ABA is also influenced by cold stress in wheat [ 220 ], heat stress in wheat [ 115 , 221 , 222 ], and salt stress in maize [ 223 ]. ABA accumulates in stressed plants, interrupts their photosynthesis, and stimulates stomata closure to reduce water loss through transpiration.…”
Section: Mechanisms Associated With Stress Tolerancementioning
confidence: 99%
“…Increased expression of genes involved in glycine, serine, and threonine metabolism under heat stress suggests the possible role of these enzyme activities and their influence on promoting some essential amino acid transportation and synthesis in response to heat stress. Previous studies in plants reported a considerable effect and possible mechanisms with the induction of amino acid synthesis in response to heat stress in plants [43,44]. We found an upregulation pattern of genes encoding enzymes involved in ascorbate and aldarate metabolism, such as UDP-sugar pyrophosphorylase (EC: 2.7.7.64), L-ascorbate peroxidase (EC: 1.11.1.11), and aldehyde dehydrogenase (NAD+) (EC: 1.2.1.3), and downregulation of GDP-L-galactose phosphorylase (EC: 2.7.7.69) at 6-h stress ( Figure S5).…”
Section: Unique Deg-enriched Pathways In V Corymbosummentioning
confidence: 99%